CHARACTERIZATION AND SOURCE IDENTIFICATION OF POLY CYCLIC AROMATIC HYDROCARBONS (PAHS) FOR COASTAL INDUSTRIAL CITY MANGALORE, INDIA - Kalaiarasan, Gopinath; M, Adarsh; Balakrishnan, Raj Mohan; Krupadam, R (MATTER: International Journal of Science and Technology, 2017)
Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous environmental pollutants generated primarily during the incomplete combustion of organic materials. These compounds are contributed to the atmosphere due to various anthropogenic activities in the form of particulate matter. In this study Particulate matter, PM10 samples were collected from a Traffic site (Town hall) and Industrial site (KSPCB) of a coastal city Mangalore in India during post the monsoon period between October to December 2014. The samples were analysed for PAHs namely seven Fluorene (Flu), Acenaphthene (Ace), Chrysene (Chr), Benz(a)anthracene (B(a)A), Benzo(a)pyrene (B(a)P), Benzo(b)fluoranthene (B(b)F), Indeno (1,2,3-c,d) and pyerene (Ind) using fluorescence spectrophotometer. The quarterly average of TPAHs concentration of the industrial site varied from 12 ng/m3 to 109 ng/m3 with an average of about 70.2 ng/m3 whereas TPAHs concentration of traffic site varied from 39 ng/m3 to 252 ng/m3 with an average of 109 ng/m3. Further it was observed that the TPAH concentrations showed increasing trend TPAHoct < TPAHNov < TPAHDec due to meteorological factors. Concurrently TPAH concentrations at traffic site was 1.8 times higher than that of the industrial site. The source apportionment study carried out using Principal Component Analysis (PCA) assisted by varimax rotation revealed that there were only two types of principal components PC1 and PC2. Both the PCs were observed to have variances of 66.21% and 14.38% respectively and classified to originate from fossil fuel burning predominantly diesel/petrol combustion in vehicles for traffic site and the rest from other type of fuels for the industrial site.